Comparison of real-time ultrasound approach to non ultrasound-assissted approach in paramedian lateral spinal anaesthesia for lower limb surgery - Soon Eu, Chong (2015)

(untitled)
Title: Comparison of real-time ultrasound approach to non ultrasound-assissted approach in paramedian lateral spinal anaesthesia for lower limb surgery. Background: Real-time ultrasound-guided neuraxial blockade remains a largely experimental technique. We investigated if this technique might improve the approach of spinal anaesthesia in different aspects. Objectives: To compare the clinical efficacy of real-time ultrasonographic localization of the intrathecal space by comparing success rate, first needle pass and immediate complications. Methods: 60 patients with BMI less than 30 kg/m2 undergoing lower limb surgery under spinal anaesthesia were recruited. Following palpation and a pre-procedural ultrasound scan, a spinal needle introducer was inserted in-plane to the ultrasound probe. The angle of introducer was adjusted in real-time until it pointed in between two vertebral laminae. A 25G Pencan spinal needle was inserted. Successful dural puncture was confirmed by backflow of cerebrospinal fluid. This was compared to paramedian spinal anaesthesia via palpation method. Results: There were no differences in age, weight, height, BMI, or ASA grading between the two groups. Successful dural puncture on first skin puncture was significantly higher in the ultrasound group than palpation group (86.7% vs. 43.3%, P<0.01). The success rate of single needle pass was also significantly higher in the ultrasound group (46.7% vs. 20%, p=0.028). Among the overweight (BMI>25) patients, dural puncture was successful on the first skin puncture in 17 patients (85%) in ultrasound group vs. 6 patients (33.3%) in palpation group. (p=0.001). Successful rate of single needle pass was also significant in ultrasound group (50% vs. 16.7%, p = 0.033). Amongst patients with BMI<25, there were no significant difference in both groups. Duration taken for determining puncture site was (0.69+1.01) minutes in the ultrasound group and (1.60+1.19) minutes in the palpation group. (p=0.002). Conclusion: Real-time ultrasound-guidance improves the success rate of paramedian spinal anaesthesia in lateral position, especially in overweight patients. It has not much of role in patients who are thin and have easily palpable spinous process.